ANALYZING LEADERSHIP STYLE AND EMPLOYEE PERFORMANCE (Study at PT. Bank Mandiri Area Manado (Persero) Tbk.) - Karisoh, Gabriel Dave Janma (Universitas Sam Ratulangi, 2016)
: In this global era, every organization seeking to improve the quality of work of employees in order to generate productive employee. Employees play a major role in running the organization. Therefore, their productivity must be increased in order be well performed. This study aims to determine the influence of leadership style and employee performance. In this study, population where is drawn for employees of Bank Mandiri Area Manado, Data was conducted by interviews with 15 respondents. This research utilizes a qualitative approach to examine and explore experience in-depth interviews. The results and conclusion showed that the Leadership Style significantly effect employee performance. While employee performance is also influenced by the working environment and employee engagement. Mangement of Bank Mandiri Area Manado Â should apply democratic leadership style to their employees and include them in decision-making process. In order to create a conducive working environment and leaders to be more productive. While employees must continue doing the best and motivating each other to be rewarded by Bank Mandiri Area Manado because of their performance. Â Keywords: human resources management, leadership, leadership style, employee performance